Multi-disciplinary investigations of active faults in the Julian Alps, Slovenia - Cunningham, Dickson; Gosar, Andrej; Kastelic, Vanja; Grebby, Stephen; Tansey, Kevin (Academy of Sciences of the Czech Republic, 2007)
UK-Slovenian collaborative research connected to EU COST-Action 625 began in 2003 and has involved interdisciplinary research into the current activity, structural architecture and landscape expression of the Ravne and Idrija strike-slip fault systems in NW Slovenia. The Ravne fault may be the best exposed actively propagating strike-slip fault system in Europe and through combined structural fieldwork, earthquake seismology and airborne LiDAR (Light Detection And Ranging) surveys, a new understanding of the fault’s along-strike segmentation, three dimensional geometry and stepover zone kinematics has been gained. The Idrija Fault in contrast, is poorly exposed, but defines a regional lineament with an intensely brecciated fault core; it may have been responsible for the largest historical earthquake to have ever affected the region. High-resolution LiDAR images recently obtained for both fault systems allow for efficient focussed fieldwork and future work will be devoted to documenting the timing of previous earthquakes and the connectivity and displacement transfer between active faults at the NE corner of the Adria microplate.